Crack growth process in GBF area of SUJ2 bearing steel in very high cycle fatigue regime. (December 2013) - Li, Y D; Guo, W M; Xu, N; Wu, X F; Shi, J B; Ma, H
Abstract : The crack growth process in GBF of high strength bearing steel JIS SUJ2 is qualitatively investigated by low–high two-step variable amplitude loading (TSAL) tests. It is demonstrated that the GBF size reduces with the increase in applied stress amplitude, and that the GBF size at a given stress amplitude is a constant which is independent of inclusion size at the crack origin. The fatigue life at a given stress amplitude, which is proportional to −8 power of the inclusion size, reduces with increasing inclusion size. It was shown by TSAL tests that GBF was formed at the earlier stage (approximate 10 5 cycles corresponding to less than 1% total fatigue life in the regime N f ≧10 7 cycles) and propagated hardly until near to the final life (more than 90% total fatigue life). After that the GBF crack will propagate rapidly to the ultimate size in a short time.